CONFICIUS IN THE 21 ST CENTURY - VOSKANYAN, SHOGHIK (Main Issues Of Pedagogy And Psychology, 2015)
The article is devoted to Confucius who is considered to be the symbol of unity and ideological strength, as well as the founder of moral and religious teachings, who was one of China’s progressive and stylish currents. He has made a great contribution to the spiritual and cultural life ofChinese people. Like all the ancient philosophers Confucius has also left no written works, except his tales which aer about social, political and economical life of Chinese people.